Molecular Evolution of Pseudomonas syringae Type III Secreted Effector Proteins - Dillon, Marcus M.; Almeida, Renan N.D.; Laflamme, Bradley; Martel, Alexandre; Weir, Bevan S.; Desveaux, Darrell; Guttman, David S. (Frontiers in Plant Science, 2019)
Diverse Gram-negative pathogens like Pseudomonas syringae employ type III secreted effector (T3SE) proteins as primary virulence factors that combat host immunity and promote disease. T3SEs can also be recognized by plant hosts and activate an effector triggered immune (ETI) response that shifts the interaction back toward plant immunity. Consequently, T3SEs are pivotal in determining the virulence potential of individual P. syringae strains, and ultimately help to restrict P. syringae pathogens to a subset of potential hosts that are unable to recognize their repertoires of T3SEs. While a number of effector families are known to be present in the P. syringae species complex, one of the most persistent challenges has been documenting the complex variation in T3SE contents across a diverse collection of strains. Using the entire pan-genome of 494 P. syringae strains isolated from more than 100 hosts, we conducted a global analysis of all known and putative T3SEs. We identified a total of 14,613 putative T3SEs, 4,636 of which were unique at the amino acid level, and show that T3SE repertoires of different P. syringae strains vary dramatically, even among strains isolated from the same hosts. We also find substantial diversification within many T3SE families, and in many cases find strong signatures of positive selection. Furthermore, we identify multiple gene gain and loss events for several families, demonstrating an important role of horizontal gene transfer (HGT) in the evolution of P. syringae T3SEs. These analyses provide insight into the evolutionary history of P. syringae T3SEs as they co-evolve with the host immune system, and dramatically expand the database of P. syringae T3SEs alleles.